Socio-economic and Public-power Aspects of the State and Society Relations in Modernizing Russia - Lyubashits, Valentin Y.; Mamychev, Alexey Y.; Vronskaya, Maria V.; Timofeeva, Alla A. (International Review of Management and Marketing, 2016)
The paper discusses the socio-economic and publicly-power aspects of the state and society relations in the modernized Russia traced the process of formation and development of corporate democracy. As a key problem is pointed out that Russia is predisposed to the state, paternalistic oriented model of economic democracy, including its corporate component. It is argued that the creation and enforcement of effective legislation, “filtering” narrow group interests of any type requires a regulatory system of the state. Such activities of the Russian state could lead to the realization of the absolute principle of “inviolability” of the property that adequate non-interference of the state in the current framework of democratic institutions. Separately, in the work it provides a comparative analysis of the formation of corporate democracy in Eastern Europe and Russia. It is argued that the “corporate” structure, as part of a functional representation of the system are an intermediate form and they can be turned in both directions – and a “democracy of proprietors” and administrative “managed democracy”. Keywords: power, government, civil society, institution of property, corporate democracy, political system, economic processes JEL Classifications: D72, K40, M14, G30